Nutritional Status of a Group of Children Under Five Suffering from Malaria in a Timor Leste District - Anagalys Ortega Alvelay; Marcos Félix Osorio Pagola; Sol Esther García Morales; Denis Monzón Vega; Mabel Vega Galindo (Medisur)
Background: Malaria is a health problem in underdeveloped countries. The child population is particularly vulnerable. Objective: to determine the nutritional status of children under five suffering from malaria who attended a clinic in Timor Leste. Method: a descriptive, correlational study was conducted. The sample consisted of 435 children under five years old, diagnosed with malaria, who attended consultation from June 2008 to July 2009. Nutritional status was evaluated. A medical history demographic, socioeconomic and Plasmodium type data was obtained. Results: 254 children (58.4%) were in the group from 2 to 4 years old. Most children (415, 95.4%) had no toilet or piped water in their homes. The average number of people living in the house is 8.3; 5.6 per room. Females were predominant with 50.3%, as well as rural children 402 (92.4%). Most children (84.6%) are undernourished. Statistical relationship was found between nutritional status and age (X2 = 7.44, df = 1, p = 0.01) and nutritional status and sex (X2 = 14.37, df = 1, p = 0, 01). A higher frequency of moderate malnutrition was observed in children with malaria (41; 61.2%). Plasmodium vivax was highly frequent, being present in 299 children (68.7%). Conclusion: children from 0 to 1 year of age are 2 to 4 times more likely to experience malnutrition. Females are between 2 and 5 times more likely to be undernourished than other children with malaria.